Origin or organoleptic characteristics of Pears : which is more valued in the market? - Botelho, Anabela (2014)
Consumers’ decision when buying fruit and vegetables is determined by tangible and intangible attributes. In general, intangible attributes, such as the origin of the variety, are not perceived by consumers before or after purchase; thus, information on these characteristics of products must be provided. The origin of the variety is a particularly important intangible attribute in the case of fruit and vegetables. Its relevance is due to the role that traditional varieties may play in the conservation of biodiversity, and also in the local economy. In many instances, however, the higher production costs and lower profitability associated with traditional varieties discourage the continuation of this activity. Arguably, the farmers shall then be compensated by the market (through a price premium) to ensure the maintenance of local traditional varieties. The purpose of the present study is to enhance information about the relative importance of several attributes or characteristics of the product Pears, and to assess consumers’ willingness to pay for the specific attribute Origin of Variety, detecting and quantifying the potential existence of a price premium.